Pemberdayaan Guru Migran Melalui Pelatihan Media Pembelajaran Berbasis Budaya: Kolaborasi Pengabdian Internasional - Ananda, Refisa; Tatminingsih, Sri; Yekti Kwasaning Gusti, Valeria; Wardani Simarmata, Sari; Bavo Priyana, Efraim (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance the skills of migrant teachers in Sabah, Malaysia, in designing and implementing learning media that integrate elements of Indonesian culture into classroom teaching practices. The implementation method employed Participatory Action Research (PAR) combined with a needs-based participatory training approach. Evaluation instruments included pre-tests and post-tests, which were analyzed using both quantitative and qualitative descriptive methods. The results of this community service activity showed improvements in teaching strategies, increased student engagement, and stronger connections with Indonesia’s cultural heritage. By integrating Indonesian cultural values into the learning process, this program not only enhanced teachers’ professional competencies but also fostered a sense of pride and national identity among students, helping them maintain a connection with their homeland while living abroad.